Temporal lobe epilepsy with amygdala enlargement: A systematic review. (13th May 2021) - Chakravarty, Kamalesh; Ray, Sucharita; Kharbanda, Parampreet S.; Lal, Vivek; Baishya, Jitupam
Abstract: Temporal lobe epilepsy (TLE) with enlargement of the amygdala (AE) is a distinct clinical entity with contrasting clinical features from TLE with hippocampal sclerosis (HS). The objectives of this systematic analysis were to study the clinical characteristics and treatment outcome of people with TLE with AE. Pubmed, Embase, Cochrane, Web of Science, Scopus, and Medline were searched using the keywords amygdala enlargement, temporal lobe epilepsy, epilepsy, and seizure in November 2020. We found 18 studies that satisfied the inclusion criteria. A total of 361 patients were included in this analysis. The mean age of onset was 36.2 years, and febrile seizure was uncommon compared to TLE with HS subjects. The type of aura and automatism was similar to TLE with HS, though less prevalent. Electroencephalography (EEG) was usually concordant with the side of AE. Anti‐seizure medications (ASM), surgical, and immunotherapy were used in different studies. 86 patients underwent surgery with Engel I outcome in 69.7%. Histopathology of the resected samples was predominantly dysplasia and gliosis. A group of patients that responded well to immunotherapy with subsequent reduction of amygdala volume (AMV) purported an autoimmune etiology of AE. Heterogeneity was the main drawback that prevented comparability among the studies. The methods of measurement of AMV also differed widely in the included studies, and standardization of its method is still lacking. This analysis suggests TLE with AE as a distinctive group of patients either due to a developmental anomaly or autoimmune etiology.